ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI INKLUSIF (STUDI KASUS: KABUPATEN/KOTA DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA 2012-2021) - Amin, Nurul Hasby Hilmy; Nurman Setiawan Fadjar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Indonesia as a developing country that has 34 provinces with many remote, outermost and lagging areas has problems with the impact of high economic growth, namely poverty, inequality, and unemployment. Likewise with the DI Yogyakarta Province which experienced this condition. The concept of inclusive economic growth exists as growth creating broad access and opportunities for all levels of society in an equitable manner, increasing welfare, and reducing disparities between groups and regions. This study aims to analyze the effect of the independent variables consisting of the minimum wage, human development index, and per capita income on the dependent variable inclusive economic growth. The method used is panel data regression analysis. The results showed that the minimum wage variable had a negative and significant effect on inclusive economic growth, while the human development index and per capita income variables had a positive and significant effect on inclusive economic growth